Measurement of hematopoietic progenitor cells using XN2000 hematology analyzer. (18th August 2021) - Al Mamari, Sahimah; Al Saadi, Ahoud; Al Zaabi, Rua; Al Jamalani, Alshaima; Al Qassabi, Jamal; Pathare, Anil; Al‐Khabori, Murtadha
Abstract: Introduction: Stem cell enumeration by the hematopoietic progenitor cells (HPC) mode is a novel method available from Sysmex XN2000 hematology analyzer. A small amount of blood (190 μL) is required, and the results are available in a few minutes without manual gating or presample treatment. The present study compares stem cell measurements using XN2000 analyzer HPC mode and FC500 flow cytometry analyzer using peripheral blood (PB) specimens and apheresis products. Methods: In this prospective study, CD34‐positive cell counts were enumerated using an FC500 flow cytometry analyzer and compared with XN2000 Sysmex analyzer (XN‐HPC mode) in the same samples. Results were compared using Bland‐Altman plots. Results: A total of 103 samples were used. In the PB samples, the median HPC count and CD34‐positive cells were 83.5 × 10 6 /L and 78.0 × 10 6 /L, respectively. The mean Bland‐Altman difference was 4.5 × 10 6 /L (Limits: −51.7 to 60.7 × 10 6 /L), with a Pearson's correlation of 0.79. In the apheresis products, the median HPC count and CD34‐positive cells were 1468 × 10 6 /L (IQR: 1049 ‐ 1960 × 10 6 /L) and 1327 × 10 6 /L (IQR: 910 ‐ 2001 × 10 6 /L), respectively. The mean Bland‐Altman difference was 179.0 × 10 6 /L (Limits: −2022.2 ‐ 2380.2 × 10 6 /L), with a Pearson's correlation of 0.58. Conclusion: The XN‐HPC mode has an excellent correlation and minimal disagreement for stem cell enumeration in PB compared with flow cytometry and could replace it. There is high disagreement in apheresis products, and therefore, the XN‐HPC mode cannot be recommended.